Enhanced Radiation Resistance of Methanosarcina soligelidi SMA-21, a New Methanogenic Archaeon Isolated from a Siberian Permafrost-Affected Soil in Direct Comparison to Methanosarcina barkeri - Morozova, Daria; Moeller, Ralf; Rettberg, Petra; Wagner, Dirk (Astrobiology, 2015)
Permafrost-affected soils are characterized by a high abundance and diversity of methanogenic communities, which are considered suitable model organisms for potential life on Mars. Methanogens from Siberian permafrost have been proven to be highly resistant against divers stress conditions such as subzero temperatures, desiccation, and simulated thermophysical martian conditions. Here, we studied the radiation resistance of the currently described new species Methanosarcina soligelidi SMA-21, which was isolated from a Siberian permafrost-affected soil, in comparison to Methanosarcina barkeri, which is used as a reference organism from a nonpermafrost soil environment. Both strains were exposed to solar UV and ionizing radiation to assess their limits of survival. Methanosarcina soligelidi exhibit an increase in radiation resistance to UV (2.5- to 13.8-fold) and ionizing radiation (46.6-fold) compared to M. barkeri. The F₁₀ (UVC) and D₁₀ (X-rays) values of M. soligelidi are comparable to values for the well-known, highly radioresistant species Deinococcus radiodurans. In contrast, the radiation response of M. barkeri was highly sensitive to UV and ionizing radiation comparably to Escherichia coli and other radiosensitive microorganisms. This study showed that species of the same genus respond differently to UV and ionizing radiation, which might reflect the adaptation of Methanosarcina soligelidi SMA-21 to the harsh environmental conditions of the permafrost habitat.